2018
DOI: 10.1108/jpbafm-02-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Institutional isomorphism and cash management practices in Mississippi

Abstract: Purpose The purpose of this paper is to draw on the theory of institutional isomorphism to investigate how Mississippi’s centralized cash management policy affects the cash management practices in the state’s rural and urban counties. Design/methodology/approach The study uses a sequential exploratory mixed methods design involving a qualitative documentary analysis and a quantitative analysis of a survey of Mississippi counties. Findings The study finds that institutional isomorphism drives cash managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Although a difference is reported among emergency management and public health professionals favoring the former, this is weak as is the strength of association (χ 2 = 9.33; p < .1; Somers’ D = 0.05). The lack of significance regarding these indicators may be because professional training levels off any differences that these variables might cause and confirm what prior studies have found about professional training as a source of normative and mimetic isomorphism (Nukpezah & Abutabenjeh, 2018).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Although a difference is reported among emergency management and public health professionals favoring the former, this is weak as is the strength of association (χ 2 = 9.33; p < .1; Somers’ D = 0.05). The lack of significance regarding these indicators may be because professional training levels off any differences that these variables might cause and confirm what prior studies have found about professional training as a source of normative and mimetic isomorphism (Nukpezah & Abutabenjeh, 2018).…”
Section: Resultssupporting
confidence: 85%
“…Like previous studies, the study finds merit in measuring coordination effectiveness using professional informed judgment in their role representing their organizations (K. Kim et al, 2017; Nukpezah & Abutabenjeh, 2018), which makes the variable latent.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…A total of 124 respondents, representing about 38% response rate, completed the survey. The response rate compares well with previous surveys of local government officials (Nukpezah and Abutabenjeh, 2018). Some respondents did not complete the personal information section, but the results indicate that the respondents were gender-balanced (52% male and 44% female) and were representative of the types of local government represented in the network (48% county employees and 52% city employees).…”
Section: Methodssupporting
confidence: 77%
“…With the increasing use of technology in contemporary public management, the connection between the use of smart cities technologies and economic development needs further articulation. Because local economic development policy decisions are made by city officials whose professional training and opinions influence policies that are advocated and eventually passed (Nukpezah & Abutabenjeh, 2018; Pagano & Bowman, 1995), their perceptions about the connection between smart cities technologies and economic development likely influence policy priorities and budgetary allocations and are, therefore, important. Consequently, research that focuses on the innovative use of technology in fostering economic development in local governments is essential, particularly with reference to the perception of chief administrative officers (CAOs).…”
mentioning
confidence: 99%